Explorer les parcours thérapeutiques des enfants atteints de cancer au Burkina Faso - Marie-Thérèse Arcens Somé; Aude Nikiema (EchoGéo)
The health system, in Burkina Faso, is based on a large number of nearby basic healthcare facilities, but they treat conditions that do not require surgical intervention and are communicable diseases. We therefore wondered how the care of children suffering from other diseases, in this case cancer, unfolds. Interviews were conducted in the capital, Ouagadougou, with children suffering from cancer, their families and healthcare staff. The therapeutic pathways collected were mapped, and their analysis highlights their complexity and duration. They also show that treatment is fragmented, combining conventional and traditional medicine, with specialist services often being called in too late.